Enhancing Reading Skills by Using Quizizz for Vocational School Students - Alan Damar Romadhoni Suwaji (Retain: Journal of Research in English Language Teaching, 2024)
There is a problem that students of electro department in SMKN 3 Surabaya have an issue in reading skill. Therefore, this study investigated how Quizizz work to enhance vocational school students’ reading skills. This study is done in qualitative research, so the result of this study describes the participants’ responses of Quizizz as a learning media to enhance students’ reading skills. In addition, there is a data contains the comparison of assessment about reading text assignment which is done without Quizizz and using Quizizz. The participants of this study are electro department students (TAV) in SMKN 3 Surabaya and their English teacher. The questionnaire for students is different with the questionnairer for their English teacher.The result shows that Quizizz quite helps vocational school students to enhance their reading skills.